2020
DOI: 10.3390/insects11010058
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) Colonizing Sweet Potato and Cassava in South Sudan

Abstract: Bemisia tabaci (Gennadius) is a polyphagous, highly destructive pest that is capable of vectoring viruses in most agricultural crops. Currently, information regarding the distribution and genetic diversity of B. tabaci in South Sudan is not available. The objectives of this study were to investigate the genetic variability of B. tabaci infesting sweet potato and cassava in South Sudan. Field surveys were conducted between August 2017 and July and August 2018 in 10 locations in Juba County, Central Equatoria St… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 89 publications
4
13
1
Order By: Relevance
“…pumpkin (55/70 pumpkin whiteflies), sweet potato (38/79) and tomato (14/51) but not at all to cassava (0/98). The strong association with sweet potato in the field has been noted previously (Sseruwagi et al 2006;Misaka et al 2019), and recent studies have verified that sweet potato is a preferred host for MED-ASL under laboratory as well as field conditions (Vyskočilová et al 2019;Macfadyen et al 2020). These data support the proposal of Vyskočilová et al (2018Vyskočilová et al ( , 2019 to classify MED-ASL as a distinct species from MED-Q1, due to these populations failing to interbreed, showing a distinct mtCO1 phylogenetic placement, as well as marked differences in their preferred host ranges.…”
Section: Abundance and Host Range Of Whitefly Speciessupporting
confidence: 75%
See 1 more Smart Citation
“…pumpkin (55/70 pumpkin whiteflies), sweet potato (38/79) and tomato (14/51) but not at all to cassava (0/98). The strong association with sweet potato in the field has been noted previously (Sseruwagi et al 2006;Misaka et al 2019), and recent studies have verified that sweet potato is a preferred host for MED-ASL under laboratory as well as field conditions (Vyskočilová et al 2019;Macfadyen et al 2020). These data support the proposal of Vyskočilová et al (2018Vyskočilová et al ( , 2019 to classify MED-ASL as a distinct species from MED-Q1, due to these populations failing to interbreed, showing a distinct mtCO1 phylogenetic placement, as well as marked differences in their preferred host ranges.…”
Section: Abundance and Host Range Of Whitefly Speciessupporting
confidence: 75%
“…4). MacFadyen et al (2020) also found SSA2 to be present in only a few regions of central to northern Uganda, and in neighbouring South Sudan, SSA2 was reported recently as the most prevalent (Misaka et al 2019) adding weight to the prevalence and locality of SSA2 being linked to agroecology and landscape factors rather than a chance event caused by the timing of our survey. SSA1(-SG1) is prevalent across the rest of Uganda and this is considered linked to its ability to feed on and colonise multiple host plants including cassava (Sseruwagi et al 2006;Milenovic et al 2019).…”
Section: Geographical Distribution Of Prevalent Whitefly Speciessupporting
confidence: 52%
“…2). Some studies suggest that B. tabaci IO does not use cassava as a host plant (Misaka et al 2020), however nymphs of this species were recorded on cassava and other plants throughout our study. B. tabaci SSA1 was also recorded on other crop and non-crop plants (e.g., wild groundnut, sweet potato), but often not in the frequency with which it was recorded on cassava (Fig.…”
Section: What Are the Common Species Of Whitefly Found On Cassava And On Nearby Crops And Non-crop Host Plants?contrasting
confidence: 67%
“…In Tanzania, the B. tabaci IO species was also relatively common in some cassava fields, on cassava plants. Misaka et al (2020) did not record B. tabaci IO on cassava in a survey conducted in South Sudan, however, their study focussed on collecting adults and sequenced low numbers of individuals from cassava. In our study, B. tabaci SSA2 was found relatively frequently but in low density on other crop plants and non-crop plants in cassava production landscapes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SSA2 B. tabaci whitefly possessed similar biological traits with SSA1-SG1 B. tabaci whitefly in the insectary, which corroborates field reports of high whitefly abundance associated with the two species in East Africa [ 4 , 19 , 22 , 23 ]. A few studies reported SSA2 whiteflies as the highly abundant whitefly species on cassava in Uganda (between 1997 to 1999) [ 11 ], in some areas of northern Uganda [ 22 , 23 ] and in Juba, South Sudan [ 49 ]. The study indicated SSA2 B. tabaci whitefly to have a slightly higher proportion of emerged female adults.…”
Section: Discussionmentioning
confidence: 99%